PENDUGAAN KEDALAMAN AIR TANAH DENGAN GEOLISTRIK RESISTIVITAS DI DESA TEGALWERU, KECAMATAN DAU, KABUPATEN MALANG - Dian Chandrasasi; Jadfan Sidqi Fidari; Lily Montarcih (Universitas Islam Nahdlatul Ulama Jepara, 2023)
The main problem with the availability of ground water is generally due to the relatively deep wells of residents (information from residents of more than 50 m), so that it requires very expensive production well excavation costs, especially for villagers. Many people in Tegalweru Village, Dau District, Malang Regency still have not utilized the potential of groundwater in the area. The use of clean water is still sourced from other than ground water. This is because there is no information related to the presence of groundwater. The purpose of the study was to determine the soil layer that has groundwater potential (aquifer) based on the distribution of resistivity values and can be used as a basis for consideration in making boreholes. Based on geoelectrical data processing and analysis, it can be concluded that the groundwater potential in the garden area has good groundwater potential by identifying several aquifer layers up to a depth of 145 meters. The geoelectric point rock lithology no. 01, 02 and 03 consists of top soil, tuff and breccia layers.